The Validity of Ethnoscience-Based Student Worksheets to Improve Student Science Literacy - Muhlis, Nur Fadhillah; Rompegading, Andi Badli; Irfandi, Rizal; Yani, Ahmad; Nasir, Muhammad; Arafah, Muhammad; Rijal, Syamsu (Unnes Science Education Journal, 2023)
Based on the facts on the ground, Indonesian students have low scientific literacy skills. This is shown by the 2018 PISA data which explains that the score of Indonesian students is 396 below the PISA average score of 500 and is ranked 70 out of 78 countries. Therefore, teachers must improve students’ scientific literacy skills so that students’ understanding of science can be trained so that they can keep up with the times. The purpose of this study was to improve the scientific literacy skills of class VII students through the development of ethnoscience-based student worksheets. The method used is a combined quantitative and qualitative method, through validation methods by two expert lecturers and analyzed descriptively quantitativel, with a 3D development model (define, design, and develop). The results showed that the validation of student worksheets was in the very valid category with a percentage of 85%. Based on these results, the worksheets of students based on ethnoscience are appropriate to be used as learning media to improve students’ scientific literacy skills.